Kepemimpinan Ideal Bagi Generasi Milenial - Kornelius Kornan Sabat (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2021)
Leadership is a sexy and attractive issue for a leader. Leadership is also indispensable in every generation. Leaders must be able to understand the changes and developments of every era, so that what is done is able to answer every challenge of that era. There are many ways to become the ideal leader for the millennial generation, but the thing that stands out or is strongest in an ideal leadership for the millennial generation is servant leadership. Ideal leadership in the melenial generation must be able to adapt to the demands and developments of the times. Moreover, in the current millennial era, a leader who has a visionary spirit and thoughts is needed. A leader who is ready and willing to change according to the era in which God is entrusted to lead. Without the changes made, it is impossible for his leadership to be as ideal as expected in his generation.AbstrakKepemimpinan adalah sebuah isu sexy dan menarik bagi seorang para pemimpin. Kepemimpinan juga adalah hal yang sangat dibutuhkan dalam setiap generasi. Pemimpin harus mampu memahami perubahan dan perkembangan setiap jaman, sehingga apa yang dilakukan mampu menjawab setiap tantangan jaman tersebut. Banyak cara untuk menjadi pemimpin yang ideal bagi generasi milenial tetapi hal yang menonjol atau terkuat dalam sebuah kepemimpinan yang ideal bagi generasi melenial adalah kepemimpinan pelayan. Kepemimpinan yang ideal pada generasi melenial harus dapat menyesuaikan dengan tuntutan dan perkembangan zaman. Terlebih lagi pada era milenial saat ini, dibutuhkan seorang pemimpin yang memiliki jiwa dan pemikiran yang visioner. Seorang pemimpin yang siap dan mau berubah sesuai dengan jaman dimana Tuhan percayakan memimpin. Tanpa perubahan yang dilakukan maka kepemimpinannya tidak mungkin bisa menjadi ideal seperti yang diharapkan pada generasinya.